ETIKA PESERTA DIDIK DALAM KITAB WASHOYA AL-ABAA LI AL-ABNAA KARYA SYEKH MUHAMMAD SYAKIR DAN RELEVANSINYA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SEKOLAH MENENGAH PERTAMA - Nasrodin Nasrodin; Triyana Triyana; Moh. Yusuf (MUMTAZ : Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the ethics of students in the book Washoya al-abaa li al-abnaa by Sheikh Muhammad Syakir and its relevance to Islamic education subjects in junior high schools. -Islamic values, such as students defying the teacher's orders, not doing assignments, and violating the rules that apply in school. This type of research is library research, the method of collecting documentation and observation data, the data sources used are primary data in the form of the Book of Washoya Al-Abaa Li Al-Abnaa and supporting data. Checking the validity of the data uses research dependence on data. Data analysis uses content, inductive and contextual analysis. This study shows that the ethics of students in the book Washoya al-Abaa Li al-Abnaa includes: 1) descriptive ethics consisting of a). glorify teachers more than parents, b). expect the blessing of the teacher, 2) normative ethics, namely: a). earnestly and enthusiastically, b). set the time, c). Reading, studying, and studying the material, d). ask and discuss, e. learn according to their level, f). comply with the rules, g). calm down, h). good behavior. While the relevance of the book Washoya al-Abaa Li al-Abnaa to PAI subjects can be used as a reference for students in learning and can apply these ethics properly.